FINANCIAL STRAIN AMONG DEMENTIA INFORMAL CAREGIVERS. (11th November 2018) - Sefcik, J; Petrovsky, D; Varrasse McPhillips, M; Hodgson, N; Gitlin, L
Abstract: Dementia informal caregivers in the community often report burden related to providing care to the care recipient. Informal caregivers may also experience financial strain, which has received little attention in the literature, despite the fact that it could contribute to poor outcomes for the dyad. We examined baseline data from the Dementia Behavior Study (NCT01893579) and caregivers' response to the question, "How hard is it for you to pay for the very basics like food, housing, medical care, and heating?" Among the 250 respondents, we found that people who self-identified as Black or African American were more than twice as likely to report having moderate to high levels of difficulty to pay their bills compared to White respondents (Chi-square p = 0.014). This finding illuminates the need for further research to understand financial strain, its relationship to race, and other contributing factors, as well consequences of financial strain